Thermal aging and chemical resistance evaluation of carbon black filled natural rubber blending: effect of the composition of acrylo nitrile and styrene butadiene rubber. Issue 1 (December 2020) - Susanto, T; Rahmaniar; Farida; Lestari, D W; Abdullah, K
Abstract: Natural rubber (NR) has excellent tensile and abrasion properties, but its thermal and chemical resistance needs to be improved. The present study investigates the effect of acrylonitrile-butadiene rubber (NBR) and styrene-butadiene rubber (SBR) composition in NR compounding filled carbon black (CB). The effect of chemical and heat resistance was examined by varying the addition of SBR/NBR (phr/phr) as follows 40/0; 35/5; 30/0; 25/15; and 20/20 into 60 phr (part hundred rubber) NR filled by 50 phr CB respectively. Compared with NR composites, SBR/NBR addition improved the hardness and density slightly. While tensile strength, modulus, abrasion resistance, and compression set decreased significantly. The volume, hardness, and physical properties were measured before and after 28 days of immersion in acidic, alkalis, and salty solutions. It was found that the higher loading SBR/NBR enhances chemical resistance. The hydrochloric and sulphuric acid immersion influenced the physical changes more vigorously. The thermal aging evaluation was observed by measuring the hardness and tensile strength at hot air circulation of 70°C for 24; 48 and 72 hours. The higher SBR/NBR loading could minimize the changes in hardness and tensile strength. To sum up, SBR/NBR addition improves the chemical and heat resistance on ternary blends.